A stylistic analysis of a wildlife conservation of a prologue and visual narrative documentary, “From Brutal Poacher to Delicate Pastry Chef” - Moodley, Visvaganthie (Penerbit Universiti Kebangsaan Malaysia, 2019)
Documentaries, like other genres, are being increasingly used by wildlife conservationists for creating awareness and influencing viewers to become active backers of wildlife protection. While there have been analyses of documentaries that focus on cinematic techniques, stylistic analyses of the language used in them have been limited. This paper analyses the prologue to the documentary, “The journey from brutal poacher to delicate pastry chef”, and the visual monologue narrative, “The Pastry Chef”, to show how the scriptwriter uses language as rhetoric to raise social consciousness amongst its audience. The paper adopts the stylistic pluralism approach which blends literary criticism, linguistic analysis and stylistic description. Leech and Short’s (2007) broad framework of linguistic and stylistic categories (i.e. lexical items, grammatical features, figures of speech and other rhetoric features and cohesiveness) is used to show how the scriptwriter creates awareness of wildlife conservation and positions people as active backers of wildlife protection. It argues that linguistic choices – such as lexical items, grammatical features and cohesive devices – and rhetoric are critical features of documentary design.